2021
DOI: 10.31941/pmjk.v11i2.1644
|View full text |Cite
|
Sign up to set email alerts
|

Keterlibatan Kader dalam Keberlangsungan Program Kesehatan Masyarakat (Studi Literatur)

Abstract: Community health workers (CHWs) are in a unique position between society and the health system. Although CHWs are positioned as the front line team for the extension of government programs in the community, there are no best practices in implementing community-based programs. This study aims to provide descriptive recommendations for the best CHW involvement models in the implementation of health programs. This research is a study of a number of related literatures that emphasize the community approach. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This highlights the need to enhance the capacity of health cadres through various activities such as training and coaching, in order to improve their knowledge and skills, including communication skills and the ability to deliver important health information to the community. 22,23 The Ambon City Health Office has made commendable efforts to disseminate health promotion materials concerning LF and MDA through various means, including banners, flyers, and social media channels. Interactive dialogues on local radio and television were employed as a strategic approach before the implementation of MDA.…”
Section: Use Of Multiple Types Of Informants and Media To Improve Com...mentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the need to enhance the capacity of health cadres through various activities such as training and coaching, in order to improve their knowledge and skills, including communication skills and the ability to deliver important health information to the community. 22,23 The Ambon City Health Office has made commendable efforts to disseminate health promotion materials concerning LF and MDA through various means, including banners, flyers, and social media channels. Interactive dialogues on local radio and television were employed as a strategic approach before the implementation of MDA.…”
Section: Use Of Multiple Types Of Informants and Media To Improve Com...mentioning
confidence: 99%
“…This was also noted in a previous study which found that men have lower adherence to LF drugs than women. 23,24 Men's higher activity outside the home may mean that they need more information on specific health topics, which could be provided by health cadres in their neighbourhood. Compared to males, females have shown higher knowledge and awareness about health-related matters.…”
Section: Difference Of Knowledge and Awareness About Lf Between Males...mentioning
confidence: 99%